Adsorptive Removal of Mercury by Zeolites and Montmorillonite - Andi Massoeang Abdillah; Zaenal Abidin; Widiatmaka Widiatmaka; Erni Johan; Naoto Matsue (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
The environmental pollution by the drainage containing heavy metals such as Hg is a serious problem in mining activities in Indonesia. We examined the effect of coexisting thiourea on the adsorptive removal of Hg by zeolites and montmorillonite. To a 100 mL of 10 mg/L (0.05 mM) HgCl2 solution in the absence and presence of 0.5 mM thiourea, different amounts of zeolite (A4, P or mordenite) or montmorillonite was added, shaken for 24 h, centrifuged, and supernatant Hg2+ concentration was measured. In the absence of thiourea, the ratio of the negative charges in the adsorbents to the positive charges in Hg2+, Ads/Hg ratio, needed to attain >80% Hg2+ removal were >70 for mordenite, >1625 for P, >600 for A4, and montmorillonite showed no Hg2+ adsorption. In contrast, in the presence of thiourea, nearly 100% removal was attained at lower Ads/Hg ratios: the ratios were 1 for montmorillonite, <10 for P and <18 for A4; the presence of thiourea had little effect for mordenite. These results indicate that Hg2+-thiourea complex has extremely high adsorption affinity for negative charges of montmorillonite, A4 and P, and the complex can fully penetrate into the interlayer space of montmorillonite. However, with increasing the Ads/Hg ratio, the Hg2+ removal percentage for montmorillonite, A4 and P decreased. Therefore, for the effective removal of  Hg2+ in the presence of thiourea, the choice of adsorbents and the dose of the adsorbents should be carefully determined.